Selektionsuntersuchungen an Kabeljau und Rotbarsch in grönländischen Gewässern - Dahm, E. (1991)
Johann Heinrich von Thünen-Institut, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery research in 2010